Antidiabetic action of combined medicine glikverin in terms of experimental Diabetes Mellitus type 2 - Chikitkina, O. M.; Kononenko, N. M.; Chikitkina, V. V.; Lar’yanovskaya, Y. B. (Journal of Education, Health and Sport, 2015)
Chikitkina O M, Kononenko N M, Chikitkina V V, Lar’yanovskaya Y B. Antidiabetic action of combined medicine glikverin in terms of experimental Diabetes Mellitus type 2. Journal of Education, Health and Sport. 2015;5(2):11-22. ISSN 2391-8306. DOI: 10.5281/zenodo.14893 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A11-22 https://pbn.nauka.gov.pl/works/534378 http://dx.doi.org/10.5281/zenodo.14893 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.01.2015. UDC 616.379-008.64: 615.252.349.7 ANTIDIABETIC ACTION OF COMBINED MEDICINE GLIKVERIN IN TERMS OF EXPERIMENTAL DIABETES MELLITUS TYPE 2 O M Chikitkina, N M Kononenko, V V Chikitkina, Y B Lar’yanovskaya National University of Pharmacy, Kharkiv, Ukraine medtrans2@rambler.ru Abstract Antidiabetic action of a new composition Glikverin was investigated in experimental DM in rats caused by streptozotocin on the background of nicotineamide. It was established that combination of quercetin and voglibose in one remedy determines more significant antidiabetic action than of these components separately. The influence on glicaemia level and lipid peroxidation/anbtioxidative system indexes on this model was of the same significance in Glikverin and standard reference agent tablets metformin. The efficacy of a new composition is confirmed by results of histological study. Positive influence on condition of pancreatic endocrine component in rats was more significant in Glikverin than in reference agents voglibose, quercetin and tablets metformin. Received data justifies and makes reasonable using Glikverin for correction of carbohydrate metabolism and inhibition of lipid peroxidation in terms of relative insulin resistance. Key words: experimental diabetes mellitus, oxidative stress, morphological structure of pancreas, glikverin. УДК 616.379-008.64: 615.252.349.7 АНТИДІАБЕТИЧНА ДІЯ НОВОЇ КОМПОЗИЦІЇ «ГЛІКВЕРИН» ЗА УМОВИ ЦУКРОВОГО ДІАБЕТУ 2 ТИПУ Національний фармацевтичний університет, м. Харків, Україна Досліджена антидіабетична дія нової композиції Глікверин на моделі експериментального цукрового діабету у щурів, викликаного стрептозотоцином на тлі нікотинаміду. Встановлено, що поєднання кверцетину та воглібозу в одному засобі обумовлює більш виразну антидіабетичну дію, ніж окремих його складових. Глікверин на даній моделі за впливом на рівень глікемії та показники ПОЛ/АОС не поступався за виразністю стандартному препарату порівняння таблеткам метформіну. Результати гістологічного дослідження підшлункової залози підтверджують ефективність нової композиції. За виразністю позитивного впливу на стан ендокринної складової підшлункової залози щурів Глікверин дещо переважає препарати порівняння воглібоз, кверцетин і таблетки метформіну. Отримані дані обґрунтовують доцільність застосування Глікверину з метою корекції вуглеводного обміну та гальмування вільно-радикального окиснення ліпідів в умовах відносної інсулінової недостатності. Ключові слова: експериментальний цукровий діабет, оксидативний стрес, морфоструктура підшлункової залози, глікверин. УДК 616.379-008.64: 615.252.349.7 АНТИДИАБЕТИЧЕСКОЕ ДЕЙСТВИЕ НОВОЙ КОМПОЗИЦИИ «ГЛИКВЕРИН» В УСЛОВИЯХ САХАРНОГО ДИАБЕТА 2 ТИПА Национальный фармацевтический университет, г. Харьков, Украина Исследовано антидиабетическое действие новой композиции Гликверин на модели экспериментального сахарного диабета у крыс, вызванного стрептозотоцином на фоне никотинамида. Установлено, что сочетание кверцетина и воглибоза в одном средстве обусловливает более выраженное антидиабетическое действие, чем его отдельные составляющие компоненты. Гликверин на данной модели не уступал стандартному препарату сравнения таблеткам метформина по выраженности влияния на уровень гликемии и показатели ПОЛ/АОС. Результаты гистологического исследования поджелудочной железы подтверждают эффективность новой композиции. По выраженности положительного влияния на состояние эндокринной составляющей поджелудочной железы крыс Гликверин несколько превосходит препараты сравнения воглибоз, кверцетин и таблетки метформина. Полученные данные обусловливают целесообразность использования Гликверина в условиях относительной инсулиновой недостаточности с целью коррекции углеводного обмена и торможения свободно-радикального окисления липидов. Ключевые слова: экспериментальный сахарный диабет, оксидативный стресс, морфоструктура поджелудочной железы, гликверин.